The Effect of Interactive Multimedia on Students’ Learning Outcomes Regarding the Impact of Geosphere Phenomena - Sibuea, Elvidia; Arif, Muhammad (Actual Insight, 2025)
The integration of multimedia elements in learning processes has been widely recognized for its potential to enhance student engagement and comprehension. This study investigates the effect of interactive multimedia on students’ learning outcomes related to the impact of geosphere phenomena on life. The research employed a quantitative approach using a one-group pre-test and post-test design. A total of 32 students participated in the study, and data were collected through objective tests administered before and after the use of interactive multimedia. The collected data were analyzed using simple linear regression to determine the effectiveness of the intervention. The results revealed a notable improvement in students’ scores, with the average pre-test score of 50.69 increasing to 83.75 in the post-test. Pre-test scores ranged from 25 to 70, while post-test scores ranged from 70 to 95. Statistical analysis showed a significant difference between pre- and post-test results, and the regression analysis yielded a significance value of 0.000 (p < 0.05), indicating a meaningful effect of the treatment. The R Square value of 0.462 suggests that 46.2% of the variation in student learning outcomes can be attributed to the use of interactive multimedia. These findings confirm that interactive multimedia significantly enhances students’ understanding of geosphere-related concepts in science education.